Study on Dynamic Performance of Grid Connected Doubly Fed Induction Generator - Kumar, Ashwani (My University, 2013)
Due to the environmental concern, the effort is being made to generate electricity from renewable energy sources. Among various renewable sources, one efficient alternative is wind energy. Large wind farms are being connected to grid. As the wind speed does not remain constant, Doubly-fed Induction Generator (DFIG) is being used to extract maximum power from the wind. In DFIG, the stator is directly connected to the grid while the rotor is connected through back-to back converter. The work is carried out with the objective to study the operational aspects of grid connected DFIG and simulate the dynamic performance of grid connected DFIG. The various aspects of aerodynamic conversion using wind turbine, dynamic model, converter model has been studied. The dynamic model and control scheme of grid connected DFIG has been realized under simulink environment. The stator flux oriented (SFO) and stator voltage oriented (SVO) control schemes are implemented on the rotor and grid side converter respectively. The DFIG is operated in speed control mode. The modeling and dynamic performance of the wind driven DFIG system is studied for change in wind speed, change in reference speed, change in DC link reference voltage, DC link capacitance and line inductance.
Keywords: DFIG; Vector control; SFO; Modelling and Control